2020
DOI: 10.21031/epod.662964
|View full text |Cite
|
Sign up to set email alerts
|

Rating Performance among Raters of Different Experience Through Multi-Facet Rasch Measurement (MFRM) Model

Abstract: One's experience can greatly contribute to a diversified rating performance in educational scoring. Heterogeneous ratings can negatively affect examinees' results. The aim of the study is to examine raters' rating performance in assessing oral tests among lower secondary school students using Multi-facet Rasch Measurement (MFRM) model indicated by raters' severity. Respondents are thirty English Language teachers clustered into two groups based on their rating experience in high-stakes assessment. The responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This finding corroborated with Aryadoust [ 1 ], who revealed that rater assessment could lead to different measure estimates in assessing oral presentations. In addition [ 58 ], found that raters exhibited a widespread separation in assessing student performance regarding communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborated with Aryadoust [ 1 ], who revealed that rater assessment could lead to different measure estimates in assessing oral presentations. In addition [ 58 ], found that raters exhibited a widespread separation in assessing student performance regarding communication skills.…”
Section: Discussionmentioning
confidence: 99%